2018
DOI: 10.1590/rbz4720170193
|View full text |Cite
|
Sign up to set email alerts
|

Digestible threonine for slow-growing broilers: performance, carcass characteristics, intestinal mucin, and duodenal morphometry

Abstract: Five experiments were conducted to estimate the digestible threonine requirements of slow-growing broilers: experiment 1, starter phase (days 10 to 28); experiment 2, grower I phase (days 29 to 49); experiment 3, grower II phase (days 50 to 69); experiment 4, finisher phase (days 70 to 84); and experiment 5, which was specifically conducted to determine the production of intestinal mucin over two periods (days 50 to 69 and 70 to 84). Different birds were used in all experiments. A completely randomized design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…In contrast, Machado et al . [ 28 ] reported a reduction in breast meat yields with increasing digestible threonine in the diet. Furthermore, Ramarao et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Machado et al . [ 28 ] reported a reduction in breast meat yields with increasing digestible threonine in the diet. Furthermore, Ramarao et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no effect (P>0.05) on feed intake and weight gain of quails (Table 3). Machado et al (2018) also reported an increase in the ratio height of villi / crypt depth of slow growth broiler chickens as ratio digestible Threo: Lys increased in the diets. Association of the above factors may better explain the quail´s feed improvement during this phase.…”
Section: Resultsmentioning
confidence: 82%
“…Crude mucin concentration in the excreta was measured 3 days consecutively before the sampling day proposed by Horn et al ( 22 ) and Machado et al ( 23 ). Fresh excreta were collected randomly from each replicate 2-times daily (8 am and 4 pm) in a Falcon tube and quickly chilled at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Crude mucin concentration in the excreta was measured 3 days consecutively before the sampling day proposed by Horn et al (22) and Machado et al (23). Fresh excreta were collected randomly from each replicate 2-times daily (8 am and 4 pm) in a Falcon tube and quickly chilled at 4 • C. Before collection, a clean and the sanitized plastic canvas was placed under cages to collect fresh and excreta without contamination.…”
Section: Crude Mucin Productionmentioning
confidence: 99%